Respon Eksplan Buku Durian Lahung (Durio dulcis) terhadap Konsentrasi BAP (Benzil Amino Purin) pada Media WPM (Woody Plant Medium): Response of Durian Lahung (Durio dulcis) Nodus Explant to BAP (Benzyl Amino Purine) Concentration on WPM (Woody Plant Medium) - Nofia Hardarani; Siti Nor Zahra; Raihani Wahdah; Juharni Juharni (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Lahung is a genus of endemic Durio in Kalimantan which currently has vulnerable status and is rare. Therefore, ex-situ conservation of this plant has begun using tissue culture techniques. Several things that need to be considered in in vitro propagation are the right type of explant, planting mediun and PGR. Stem nodes are generally chosen as explant because their availability does not depend on the season and has a fast response in bud induction. WPM medium is e medium intended for woody plants such as durian lahung. BAP is a PGR from the cytokinin group which is quite avtive and the most widely used. This research aimed to determine the best response of the durian lahung stem node culture to the BAP concentration on WPM medium. This research was designed using a rancomized block design (RBD) with one factor in the form of BAP concentration consisting of six levels, i.e. 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 ppm. Each experimental unit was repeated four times and consisted of ten planting bottles for e total of 240 planting bottles. The variables observed were the percentage of live explant aged 1-8 WPP, callus growth time, percentage of explant forming callus aged 1-8 WAP, callus and texture callus, shoot growth time and number of shoots. The results showed that callus appeared in response of the durian lahung stem node to the BAP concentration treatments.